Carbonic anhydrase activity identified in the powdered nacreous layer of Pinctada fucata - Namikawa, Yuto; Moriyasu, Kenji; Yasumoto, Ko; Katsumata, Satoshi; Suzuki, Michio (Process biochemistry (1991), 2023)
The shells of Pinctada fucata are composed of CaCO3 and several organic molecules. The organic molecules containing chitin and proteins play a significant role in shell mineralization. Nacrein was the most abundant acid-soluble protein in the nacreous layer of P. fucata. Nacrein has a carbonic anhydrase (CA) domain that catalyzes the reversible conversion of CO2 to HCO3-. A nacre powder (NP) directly obtained from the crushed shells of P. fucata showed CA activity (Km=3.44 mM and kcat/Km=920 M−1 s−1). Furthermore, the powder was thermally stable at temperatures over 70 °C and was reusable after the 10th cycle of catalysis. Fluorescence detection showed that nacrein was exposed on the surface of the powder. This result suggested that nacrein was localized on the powder surface and provided CA activity to the powder. The shell of P. fucata is a readily available material because it is industrial waste in the pearl aquaculture. Recently, CA has attracted attention as a promising material for CO2 sequestration to mitigate global warming. We propose the use of NP as a reasonable and competitive biocatalyst for CO2 sequestration. [Display omitted] •Nacre powder (NP) was obtained by crushing industrial waste shell of Pinctada fucata.•Carbonic anhydrase activity (CA) was identified in NP.•NP was thermally stable enzyme at temperatures over 70 °C.•NP was reusable after 10 cycles of catalysis.•CA was displayed on the surface of NP and provided CA activity to it.